Effects of gum arabic coating on postharvest life of eksotika papaya - Ding, Phebe; Inthiga, Jeappirakasam; Ali, Hassan Ibrahim (2007)
The present investigation was carried out to study the effect of different concentration of gum arabic (GA) as coating in prolonging the postharvest shelf life of papaya (Carica papayaL. cv Eksotika).Papayas were coated with 0,5 and 10% of GA for 2 min. The fruits were dried, wrapped with tissue paper and the packed in carton boxes and stored for 7 d at 20⁰C,RH 90% to stimulate containerization condition. After 7d, fruits were removed to 27⁰C,RH 70% for 6 dto stimulate the marketing condition .Quality characteristics on skin colour ,flesh firmness, soluble solids concentration (SSC), pH, titratable acidity (TA), vitamin C and weight loss were analyzed on day 0,7,9,11 and 13. Application of GA coating with three different concentrations on papaya had a significant effect in slowing down the skin color changes, retaining flesh firmness and fruit weight loss as compared to control fruits during the entire postharvest shelf life of papaya. Concomitantly, 10% of GA coatings showed significant results in terms of weight loss, skin color changes and firmness on papaya compared to other concentrations and the control. However, the three different concentrations of coating did not affect significantly on the physio-chemical characteristics such as pH,TA and vitamin C except SSC. Therefore, 10% of GA is the optimum concentration in prolonging the postharvest life of Eksotika papaya. GA coating can be potential prospects of organically food handling.